Survey of Italian Pediatricians on awareness, experiences and beliefs regarding direct-to-consumer genetic testing in minors (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Our study wanted to assess Italian pediatricians’ awareness, experience and beliefs regarding directto-consumer (DTC) genetic tests (GT) in minors, with a focus on those for predisposition to complex disease, lyfestyle, athletic ability and other inborn talents.Methods: A 28-item questionnaire was administered through the SurveyMonkey® web platform to the 9,086 members of the Italian Society of Pediatrics for which a valid email address was available. The survey was opened from April through November 2017. Statistical analyses were performed using the Graphpad software package.Results: 36.2% of the 442 respondents were aware of DTC-GT, but only 23.1% of them felt adequately prepared to meet families’ information needs. The first three sources of knowledge were the Internet (20.98%), magazines/ newspapers (16.78%) and TV/Radio (14.33%), while companies’ direct marketing activity influenced knowledge only in 2.45% of the cases. Only 16.4% of the aware respondents had been already approached for advice. More than 95% of the pediatricians who were aware would not advise DTC-GT for lifestyle, athletic performance or other inborn skills. 69.2% was unfavourable to susceptibility tests for complex diseases. Most of them expressed an interest in learning more and indicated as preferred sources of information public policies issued by professional societies.Conclusion: The low awareness and experience and the vendors’ tiny contribution to knowledge suggest a still limited penetration of DTC-GT companies in Italy. A great interest in learning more was found. Scientific societies are best positioned to support health professionals in this educational goal thanks to their role of trusted sources of information and guidance.